Asuhan Keperawatan Pada Pasien Stroke Hemoragik Dengan Pemberian Intervensi Posisi Miring Kanan Kiri Terhadap Pencegahan Dekubitus - Laily Maftuhah; Mey Nurrohmah; Dwi Wahyuni (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
The background of this research is based on a brain disease, namely stroke. Stroke results in much higher mortality and morbidity. Viewed from the aspects of risk of death, high medical costs, decreased quality of life and increased prevalence, stroke has a broad impact. Apart from that, decubitus problems also arise in stroke sufferers due to prolonged pressure, the parts that experience bruising are the hips, buttocks, foot joints and heels. Based on a preliminary study conducted at the Tangerang Regency General Hospital, there were 89 patients with a diagnosis of stroke starting from 2022. Meanwhile, in the Cempaka room, it was found that during the assessment there was 1 case with a diagnosis of stroke on January 2 2024. The results of this research are effectiveness. right and left tilt positions in reducing pressure sores or decubitus in patients with stroke. The conclusion of this study is that the right and left side positions are non-pharmacological techniques for reducing pressure ulcers or decubitus and can be used in patients who experience problems with prolonged bed rest. The suggestion from this research is that intervention in right and left tilt positions can be carried out according to the 2021 PPNI SOP.